Concentration distribution of particles in pipe flow - Chanh, Truong Minh (Vietnam Journal of Mechanics, 1980)
This paper deals with the construction of a generalized diffusive theory of micro-fluid polar mixtures. The results of the problem on the concentration distribution of particles in pipe flow are given. These results are obtained in arcordance with the experimental values.